2008
DOI: 10.1158/1078-0432.ccr-07-1849
|View full text |Cite
|
Sign up to set email alerts
|

Molecular, Pathologic, and Clinical Features of Early-Onset Endometrial Cancer: Identifying Presumptive Lynch Syndrome Patients

Abstract: Purpose: A woman with early-onset endometrial cancer (EC) may represent the ''sentinel''cancer event in a Lynch syndrome kindred.The aim of this study was to determine the incidence of Lynch syndrome in a series of young-onset EC, and to identify molecular, clinical, and pathologic features that may alert clinicians to the presence of this disorder. Experimental Design: Patients with EC, ages V50 years, were identified from the Queensland Centre for Gynaecological Cancer. Tumor sections underwent histopatholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 47 publications
(43 reference statements)
2
61
1
Order By: Relevance
“…There is evidence that MSI and immunohistochemical analysis of the MMR genes are techniques with good sensitivity and specificity for identifying patients with LS. A study carried out in 183 women with endometrial cancer [21] found a concordance of 100% between the two techniques, and Walsh et al [22] reported a similar result (97.5%). In contrast, we found less strong concordance (88.31%).…”
Section: Discussionmentioning
confidence: 93%
“…There is evidence that MSI and immunohistochemical analysis of the MMR genes are techniques with good sensitivity and specificity for identifying patients with LS. A study carried out in 183 women with endometrial cancer [21] found a concordance of 100% between the two techniques, and Walsh et al [22] reported a similar result (97.5%). In contrast, we found less strong concordance (88.31%).…”
Section: Discussionmentioning
confidence: 93%
“…Earlier studies on tumors arising in individuals with Lynch syndrome indicate that these cancers tend to be of endometrioid histology, higher grade, and with a higher risk of lymphatic invasion and tumor infiltrating lymphocytes [9]. Shih et al reported that patients under the age of 40 with loss of MMR gene expression demonstrated poor prognostic features and had a worse survival than patients with intact MMR expression [4].…”
Section: Discussionmentioning
confidence: 99%
“…20 Patients exhibiting loss of tumor expression of MMR proteins are prioritized for germline mutation testing: MLPA for genomic rearrangements and exon sequencing of the relevant MMR gene. 21 There were 439 ANECS participants identified as resident in Queensland and for whom family history questionnaire data were available.…”
Section: Study Participants and Methodsmentioning
confidence: 99%